Sosialisasi Standar dan Prosedur Keselamatan Pelayaran Penyeberangan Rute Kera Kera – Lakkang - Misliah Idrus; Fadhil Rizki Clausthaldi; Wihdat Djafar; Farianto Fachruddin; Andi Sitti Chairunnisa; Abd. Haris Djalante; Hamzah A.; Andi Dian Eka Anggriani; Rifkah Fitriah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
Lakkang is an island surrounded by rivers and has a regular mode of transportation that is used by the community to meet their daily needs in the city of Makassar. The ferry transportation (boat) used has two hulls (catamaran) with a carrying capacity of 20 passengers and 8 two-wheeled vehicles. The number of boats operating as many as 5 units of ships from the Kera-Kera pier to Kampung Lakkang with an average number of trips 4 trips per unit per day. The principle of shipping safety states that a ship that wants to sail must be in a seaworthy condition. In addition, the ship is worthy of receiving the cargo and its transportation and protecting the safety of the cargo, passengers and crew (ABK). This activity was carried out with a total of 30 participants which included boat transportation service operators, the most common being coastal communities and island communities, as well as transportation user services. Submission of service material is done by means of individual interviews. The interview process was also supported by the procurement of pocket books and pamphlets to facilitate participants' understanding of the safety materials presented. Public awareness and understanding of safety during travel during service. It is hoped that in the future the community will be able to implement shipping safety procedures on these ferry transportation services to reduce the risk of shipping accidents.